Unicompartmental Knee Arthroplasty Provides Higher Activity and Durability Than Valgus-Producing Proximal Tibial Osteotomy at 5 to 7 Years. (18th January 2017) - Krych, Aaron J.; Reardon, Patrick; Sousa, Paul; Pareek, Ayoosh; Stuart, Michael; Pagnano, Mark
Abstract : Background: The cases of patients with medial compartment osteoarthritis who were ⩽55 years old and had a proximal tibial osteotomy (PTO) or medial unicompartmental knee arthroplasty (UKA) were compared. Outcomes included postoperative activity level, function, and survivorship free of revision to total knee arthroplasty. Methods: Between 1998 and 2013, data were available for 240 patients between 18 and 55 years old with medial compartment arthritis and varus malalignment who were treated either with PTO (57 patients) or with UKA (183 patients). The mean age was 42.7 years for the 57 patients (41 men and 16 women) in the PTO group versus 49.2 years for the 183 patients (82 men and 101 women) in the UKA group. The Tegner activity level and Lysholm knee scores were evaluated at 3 months and at 1, 2, and 5 years postoperatively as well as at the time of the final follow-up. The end point for survival was defined as revision to total knee arthroplasty. A Wilcoxon rank-sum test was used to evaluate the difference between the groups with respect to the Tegner and Lysholm scores at the respective follow-up intervals. Multivariate regression was used to assess potential confounders. Results: Preoperatively, the PTO and UKA groups had similar Tegner (3.0 ± 1.3 and 2.6 ± 0.09, respectively) and Lysholm scores (69.5 ± 7.3 and 71.6 ± 5.4). Postoperatively, the UKA group had significantly superior mean Tegner scores compared with the PTO group at 3 months (3.82 and 2.02, respectively), at 2 years (4.33 and 3.75), and at the time of the final follow-up (4.48 and 3.08), while the Lysholm scores were higher at 3 months (88.0 and 76.3) and at the final follow-up (90.0 and 80.2) (p < 0.01 for all). Multivariate analysis showed UKA to be an independent predictor of activity level at 3 months, 1 year, and 2 years, as well as at the final follow-up. The survivorship was 77% in the PTO group at an average of 7.2 years and 94% in the UKA group at an average of 5.8 years (p < 0.01). The average time to failure was 98 months (range, 38 to 169 months) in the PTO group and 42 months (range, 2 to 123 months) in the UKA group (p < 0.01). Conclusions: In this comparative cohort study of young patients with isolated unicompartmental arthritis, those treated with UKA reached a higher level of activity early after surgery and it persisted at mid-term follow-up. The UKA group had earlier, but less frequent, revision to total knee arthroplasty. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.